Effects of brewing temperature and duration on quality of black tea (Camellia sinensis) and equal (50:50) combination of bush tea (Athrixia phylicoides DC.) and black tea. - Negukhula, Shonisani (My University, 2010)
Black tea (Camellia sinensis) and black tea combined with bush tea (Athrixia phylicoides) were analyzed for their polyphenol content, antioxidant activity and tannin content. Solvent extraction methods were used for extracting polyphenols, antioxidant activity and tannin content. Total phenols were determined using the Folin-Ciocalteu method, antioxidant activity using Trolox Equivalent Antioxidant Capacity (TEAC) assay and tannin content using vanillin-HCl method. Polyphenol content, antioxidant activity and tannin content were calculated using regression equation Y=MX+C, where C=intercept, Y= Absorbance of the sample and M= Gradient. Results of black tea in this study showed that total polyphenols, antioxidant activity and tannin content decreased with decrease in temperature and time and this was attributed to the release of polysaccharides at 90°C. At 90°C for 3 minutes 7.68mg/100g of total polyphenol, 3.85μmol/g of antioxidants and 2.81mg/100g of tannin were obtained and this amount decreased to 5.50mg/100mg for total polyphenols, 1.31μmol/g for antioxidant activity and 0.72mg/100mg for tannin content at 30°C for 10 minutes. Combining the two tea types (50:50) resulted in a significant (p<0.005) decrease in total polyphenols, antioxidant and tannin content. Results of this study showed that at high temperature of 90°C for 3 minutes 2.64mg/100g for total polyphenol, 2.48μmol/g for antioxidants and 1.8mg/100g for tannin were obtained and these amounts decreased to 1.39mg/100mg for total polyphenols, 0.35μmol/g for antioxidant activity and 0.64mg/100mg for tannin content at 30°C for 10 minutes. Thus high brewing temperature causes increase in total polyphenols, antioxidant activity and tannin content of the combined teas. This study showed that black tea and combined black tea and bush tea solutions had large TEAC radical scavenging activity which can be related to total polyphenols and catechins. The antioxidant activity of the tea solution increased with increase in extraction temperature and duration of soaking. It is recommended that 3-min soaking temperature of 90 °C of black tea and combined bush tea and black tea can be used due to the highest total polyphenols and antioxidant activity obtained.
Thesis (M.Sc)--University of Limpopo, 2010.
Keywords: Camellia sinensis; Athrixia phylicoides DC.; Bush tea; 635.0968; Horticulture